Fertility Differentials in India 1984 - Ministry of Home Affairs New Delhi (Ministry of Home Affairs New Delhi, 1990)
The 1984 Fertility and Mortality Study in India provides an in-depth analysis of fertility differentials across socio-economic, educational, religious, and demographic variables. Utilizing data from approximately 0.93 million ever-married women through the Sample Registration System, the study highlights notable disparities in Total Fertility Rate (TFR) and Total Marital Fertility Rate (TMFR) by religion, caste/tribe status, education, income, and urban-rural residency. Key findings reveal higher fertility among Muslims, Scheduled Castes/Tribes, illiterate women, and rural populations, with younger age at marriage significantly increasing fertility. Regional analyses from states such as Assam, Bihar, Himachal Pradesh, Karnataka, Kerala, Maharashtra, Tamil Nadu, and North-Eastern India emphasize consistent trends of reduced fertility with higher education and income, alongside urban-rural contrasts. The study underscores the critical need for targeted family planning interventions, educational outreach, and socio-economic development strategies to address regional and community-specific fertility patterns, guiding policymakers in designing effective reproductive health programs.
Vital Statistics Division Office of The Registrar General, India Ministry of Home Affairs New Delhi
Keywords: Fertility Differentials; Total Fertility Rate; Marital Fertility Rate; Socio-Economic Factors; Education; Income; Religion; Scheduled Castes; Scheduled Tribes; Urban-Rural Differences; Age at Marriage; Family Planning